PEMBUATAN BIOPELET DARI KAYU PUTIH DENGAN PENAMBAHAN GONDORUKEM SEBAGAI BAHAN BAKAR ALTERNATIF - Sofia Mustamu; Gysberth Pattiruhu (JURNAL HUTAN PULAU-PULAU KECIL, 2018)
Biopelet is one of the renewable energy alternatives that have uniformity of size, shape, density, and energy content. The purpose of this study was to examine the characteristics of biopelet consisting of a mixture of cajeput and gondorukem, and to determine the composition of the raw materials that can produce a biopelet with the best quality. The compositions of a mixture in this research are as follow 95%:5%, 90%:10%, 80%:20%, 70%:30%, 60%:40%, 50%:50%, cajeput 100% and gondorukem 100%. The manufacture of biopelet used a 20 mesh of dust with the pressure of 526.4 kg/cm2 at a temperature of 200 â—¦C for 15 minutes. Types of tests performed on biopelet include density, moisture content, volatile matter, ash content, carbon bonded, and calorific value. The results of the best quality of biopelet was in the percentage of cajeput and gondorukem was 70%:30%, tests showed densities of biopelet 0,84 g/cm3, moisture content5,89%, ash content 2,42%, volatile matter 73,99%, fixed carbon 18,96%, and calorific value 5152 kkal/kg.